Comparison of Controller and Interaction Analysis of Multi-vessel Batch Distillation - Nurul Hazwani, Sabri; Anwaruddin, Hisyam; Badhrulhisham, Abdul Aziz (Informatics Publishing Limited, 2017)
Background/Objectives: This paper is focusing on choosing the best controller and interaction analysis on multi-vessel batch distillation (MVBD). Methods/Statistical Analysis: A mathematical model is developed first by adapting simple model assumption. Open loop and closed loop models are simulated using Matlab SIMULINK. Proportional (P) and Proportional Integral (PI) are implemented on the control system. The result of closed loop is then analyzed using Relative Gain Array (RGA) method to indicate the best control loop pairing. Set point changes analysis is done to ensure the stability of controller. Findings: Two level control with two manipulated variables (reflux flow and middle vessel flow) is chosen based on the RGA analysis. Level control with PI controller gives better performance for MVBD control system. Moreover, with the presence of two level controls, the system is also able to keep the vessel holdup constant and maintain the desired product purity at a time. Application/Improvements: The study of interaction analysis can be extended to other control strategies proposed for this system. Meanwhile, the performance of the controllers can be further improve by adapting different type of tuning methods.